PERSEPSI KHALAYAK PADA PEMBERITAAN COVID-19 DI MEDIA ONLINE : Studi Fenomenologi Akun Instagram IDNTimes dan Teluuur) - Clara Benita Prastycia (2021)
This research is based on the massive amount of covid-19 news on the social media platform, instagram, during the pandemic. There exists various covid-19 news on social media, starting from IDNTimes' instagram which persuades the public's health awareness to Teluuur's instagram posts that provokes the public to break health protocols. This research aims to understand UPNVJ Communication students' perception about covid-19 contents from IDNTimes and Teluuur's instagram account. Informant's perceptions will then be associated with the experiences of students who have been previously infected by the virus and also their media literacy skills. The method used for this research is qualitative phenological method through an in-depth interview with UPNVJ Communication students. The researcher will apply the Social Judgement Theory to determine whether or not the contents from IDNTimes and Teluuur are accepted by the students. The research questions covers (1) At which media literacy stage UPNVJ Communication students are on, and (2) How UPNVJ Communication students perceive the news about covid-19 on social media. The final result of the research shows UPNVJ Communication students' agreement with IDNTimes' contents on covid-19, while disagreements rises with their perception on Teluuur's covid-19 contents.